Improvement of fiber optic sensor measurement methods for temperature and humidity measurement in microelectronic circuits - Khabay, Anar; Baktybayev, Murat; Ibekeyev, Serikbek; Sarsenbayev, Nurlan; Junussov, Nuridin; Zhumakhan, Nurzhan (Eastern-European Journal of Enterprise Technologies, 2024)
A wide range of applications such as healthcare, human comfort, agriculture, food processing and storage, and electronics manufacturing also require fast and accurate measurement of humidity and temperature. Optical fiber-based sensors have several advantages over electronic sensors, and much research has been conducted in this area in recent years. This paper describes the current trends in fiber optic temperature and humidity sensors. The evolution of optical structures aimed at humidity detection is presented, as well as a new design of an optical sensor used for this purpose. The main methods of humidity determination using fiber-optic laser reflection based on Optical fiber humidity sensor (FPI) were analyzed and experimental results were obtained. Based on temperature-sensitive strain variation, a method for temperature determination based on the specific spectral back-reflection effect of fiber Bragg gratings (FBGs) is considered. Experimental analyses were conducted on the light reflection of humidity-sensitive agarose using optical fibers based on the Fabry-Perot Interferometer (FPI). It exhibits a good linear response to relative humidity, ranging from 25 % to 95 %. During temperature measurement, the deformation changes of the Fiber Bragg Grating fibers showed excellent performance, ranging from –5 °C to 70 °C. New structures, such as resonators, are being explored to improve the resolution of fiber optic temperature and humidity sensors. In addition, recent studies on polymer optical fibers show that the sensitivity of this type of sensor has not yet been achieved. Thus, materials sensitive to humidity and temperature still need to be investigated to improve sensitivity and resolution